Virological and morphological relationships in the phases of the immune control and reactivation in patients with chronic hepatitis B - I. A. Gabdrakhmanov; A. V. Semenov; Yu. V. Ostankova; K. V. Kozlov; K. V. Zhdanov; D. A. Gusev; V. S. Sukachev; D. M. Shakhmanov; S. S. Zhabrov; A. S. Peremyshlenko; Yu. I. Bulankov; A. M. Ivanov; et al. (Журнал инфектологии)
Objective: To evaluate relationships between virological and morphological data in patients with chronic hepatitis B in phase immune control and reactivation.Materials and methods: The study involved 46 patients with chronic hepatitis B, indicators defined were content of surface antigen and hepatitis B virus DNA in the peripheral blood, the level of covalently closed circular HBV DNA in liver tissue and fibrosis stage and histological activity index (METAVIR).Results: The study found a direct correlation between the level of covalently closed circular DNA in liver puncture biopsies (number of copies per cell) and quantitative content of HBsAg in serum (r = 0,51, p = 0,03) in patients with chronic hepatitis B in phase immune control. Also in the immune control phase a direct correlation between the HBV DNA and the level of HBsAg in serum (r = 0.79, p = 0.0001) is shown. The level of covalently closed circular HBV DNA in liver puncture biopsy specimens did not differ in patients with chronic hepatitis B in the phase of immune control in the phase of reactivation (1,02 ± 0,01 copies / cell and 1,03 ± 0,03 copies / cell, p = 0.72). The index of histological activity and fibrosis were not correlated with any of the investigated virological indicator.Conclusion: Results of the study emphasized the complexity and ambiguity of the relationships between both virological and morphological indicators in patients with chronic hepatitis B, determined the direction for further study (in particular the assessment of the epigenetic regulation of the synthesis of circular covalently closed DNA), as well as set the stage for improving the principles of dynamic observing the patients with chronic hepatitis B in a phase of immune control.